PERAN KIAI DALAM PENYELESAIN SENGKETA KELUARGA PERSPEKTIF TEORI FAKTA SOSIAL EMILE DURKHIM - ahmad faqih; Badruddin; Toriquddin (Qolamuna : Jurnal Studi Islam, 2024)
This research focuses on the problem of non-continuation of marital goals and family problems in Bantaran Probolinggo District, including disputes within the family which are often rooted in incomplete or obstructed human needs such as economic, jealousy, physical, mental and social. The research uses Emile Durkheim's theory of social facts as a conceptual basis, highlighting the role of kiai as spiritual leaders, moral advisors and mediators in society. These communities tend to choose to resolve family disputes outside of court by involving kiai, who are considered public figures and respected role models. Social facts, such as ways of thinking, acting, and feeling, are considered coercive forces that control individuals and influence norms and values in society. Qualitative research methods were used, involving interviews with informants who were involved in the kiai's role in resolving family disputes. The conclusion of this research shows that the role of kiai reflects the concept of social facts in Durkheim's theory. Kiai help maintain social solidarity and guide the community in dealing with family disputes. These social facts influence individual actions, thoughts and feelings, and are related to institutions, laws, morals and political ideologies in Bantaran Probolinggo District society. Keywords : Kiai, Disputes, Social Fact Theory,